Exploring the roles of ZmARM gene family in maize development and abiotic stress response - Yu, Zhijia; Sun, Xiaopeng; Chen, Ziqi; Wang, Qi; Zhang, Chuang; Liu, Xiangguo; Wu, Weilin; Yin, Yuejia (PeerJ, 2023)
Armadillo (ARM) was a gene family important to plants, with crucial roles in regulating plant growth, development, and stress responses. However, the properties and functions of ARM family members in maize had received limited attention. Therefore, this study employed bioinformatics methods to analyze the structure and evolution of ARM-repeat protein family members in maize. The maize (Zea mays L.) genome contains 56 ARM genes distributed over 10 chromosomes, and collinearity analysis indicated 12 pairs of linkage between them. Analysis of the physicochemical properties of ARM proteins showed that most of these proteins were acidic and hydrophilic. According to the number and evolutionary analysis of the ARM genes, the ARM genes in maize can be divided into eight subgroups, and the gene structure and conserved motifs showed similar compositions in each group. The findings shed light on the significant roles of 56 ZmARM domain genes in development and abiotic stress, particularly drought stress. RNA-Seq and qRT-PCR analysis revealed that drought stress exerts an influence on specific members of the ZmARM family, such as ZmARM4, ZmARM12, ZmARM34 and ZmARM36. The comprehensive profiling of these genes in the whole genome, combined with expression analysis, establishes a foundation for further exploration of plant gene function in the context of abiotic stress and reproductive development.
Keywords: Maize (Zea mays L.); Armadillo; Abiotic stress; Development